Projeto e análise de uma fonte chaveada em alta frequência para laboratório de ensino com saídas: ± 12 V, ± 5 V, ± 3,3 V e variável até 25 V - Pozzatti, Evandro (2015)
This paper presents the study and development of a switched-mode power supply in high frequency using a not isolated DC-DC converter, buck type with 100 W output power, variable output voltages up to 25 V and symmetrical ± 12 V, ± 5 V ± 3.3 V. It is presented the project design and the operation analysis, as well as the control strategy using pulse-width modulation (PWM). The objective of this project is the use in several applications, aimed mainly as a benchtop power supply for the students of Electronics Engineering course at the Federal Technological University of Paraná – UTFPR Campo Mourão campus. The power supply operated within the expected parameters, showing well-regulated and well-filtered output voltages.